Selenium and other antioxidant issues - Ceen, C. L. (1996)
In this talk the effect of select antioxidant supplements on exercise-induced tissue oxidative damage is reviewed. Evaluation of the putative value of selenium and other essential mineral supplements is also emphasized. Similar to the case for selenium, several investigators have suggested that supplementation of zinc, copper, and/or magnesium may be of benefit to the athlete with respect to the attenuation of exercise-induced tissue oxidative damage.14 These theories will be briefly reviewed.